(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
The article examines interaction between the state and civil society institutions in Uzbekistan in comparison with European practices of participation. Its purpose is to identify procedures that transform public dialogue from a formal ritual into a mechanism of political learning. It is shown that institutional resilience is determined by the rules of consultation, the practice of reasoned response, and the possibility of public expertise.